ANALISIS TEKNOLOGI PENGOLAHAN LIMBAH CAIR PADA INDUSTRI TEKSTIL (STUDI KASUS PT. ISKANDAR INDAH PRINTING TEXTILE SURAKARTA) - Junaidi, Junaidi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
Industrial  activities  which  grow  rapidly  caused  contamination  of  environment  generated  by throwing away industrial disposal. PT. IskandarIndah Printing Textile as one of the textile factory at Surakarta managed their waste water by processing it used waste water treatment plant, so that  fulfilled  quality standard.  Characteristic  waste  water  divided  to  become  physics characteristic, chemical, and biological. Unit processing of waste consist of unit operate and unit process.  Operation  unit  consist  of ekualisasi,  koagulasi,  flokulasi,  sedimentation,  and  aerasi. While for  the  unit  of  process  cover processing  of  biology  and  processing  of  chemistry.Waste water  treatment  plant  at  PT.  Iskandar Indah  Printing  Textille  Surakarta  consist  of  unit  of ekualisasi,  koagulasi,  flokulasi,  primary sedimentation,  netralisasi,  biological  basin,  secondary sedimentation, rapid sand filter, and sludge drying bed. Quality efluent of waste water treatment plant, measured to pass efluen sand  filter, because this unit represent last unit.